2004
DOI: 10.1196/annals.1329.020
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity Stimulates Osteoblast Phenotype Expression: A Therapeutic Hint for Disuse Bone Atrophy

Abstract: Physiological actions of osteoblasts are disordered by gravity unloading. We investigated the possibility that the appropriate level of hypergravity could improve osteoblast functions that are susceptible to mechanical unloading. We evaluated hypergravity effects on the 1alpha,25-dihydroxyvitamin D(3) (VD)-inducible osteocalcin expression of primary rat osteoblasts. Cell culture plates were centrifuged for 24 h at 3, 6, 12, 24, and 48 g in a 37 degrees C incubator. The mRNA levels were analyzed by quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
2
11
1
Order By: Relevance
“…The finding that the OSVDR antiresorptive phenotype was not evident on endocortical or periosteal surfaces is consistent with effects of the transgene to locally reduce the bone proresorptive response to a systemic rise in active hormonal vitamin D levels. Mechanical load–responsive alterations in VDR expression have been reported, with microgravity suppressing (22) and hypergravity stimulating VDR activity (23) . These recent reports are consistent with our earlier observation of increased periosteal bone formation and enhanced mid‐diaphyseal diameter and strength in OSVDR long bones, which suggested enhanced load responsiveness in OSVDR cortical bone (13) .…”
Section: Discussionsupporting
confidence: 89%
“…The finding that the OSVDR antiresorptive phenotype was not evident on endocortical or periosteal surfaces is consistent with effects of the transgene to locally reduce the bone proresorptive response to a systemic rise in active hormonal vitamin D levels. Mechanical load–responsive alterations in VDR expression have been reported, with microgravity suppressing (22) and hypergravity stimulating VDR activity (23) . These recent reports are consistent with our earlier observation of increased periosteal bone formation and enhanced mid‐diaphyseal diameter and strength in OSVDR long bones, which suggested enhanced load responsiveness in OSVDR cortical bone (13) .…”
Section: Discussionsupporting
confidence: 89%
“…Fitzgerald obtained the same results after centrifugation (maximum of 3 g) for 3 h (Hughes-Fulford 2003). These results indicated that a small magnitude mechanical stimulation can alter mRNA levels in osteoblastic cells; however, these results were in sharp contrast with the results obtained from longer and higher level of hypergravity (Morita et al 2004). Furutsu et al (2000) found bidirectional effects of hypergravity on the growth and differentiated functions exist in ROS17/2.8 cells according to the magnitude of the hypergravity.…”
Section: Discussioncontrasting
confidence: 83%
“…Osteoblastic MG-63 cells show a decreased response to 1,25(OH) 2 D 3 under microgravity (2,18,26). Exposure to 12G hypergravity increases the mRNA expression of VDR and its target gene, osteocalcin, in rat osteoblasts (23). Thus microgravity decreases and hypergravity increases expression of some VDR target genes.…”
Section: Discussionmentioning
confidence: 97%